The Model of Student Satisfaction - Basneldi, Basneldi; Firdiansyah Suryawan, Ryan; Setiadi, Bekti; Muchdir, Muchdir (Opción, 2019)
The purpose of this study to determine the effect of price on satisfac- tion, marketing promotions on customer satisfaction and brand to the satisfaction of the student trainee Merpati Training center in Jakarta. The method used in this research is quantitative and analysis in this study using LISREL 8.8 software. Results in the t-test showed H1 price (HRG) to the satisfaction (KP) is rejected, H2 promotion (PRO) to the satisfaction (KP) is received, H3 price (HRG) to the brand (BRAND), H4 sale (PRO) to the brand (BRAND ) refused and brand (bRAND) to satisfaction (KP) is received, from the above results it is concluded factor of the price offered, do not get satisfaction or positive response from the students, and promotion is done at this time does not affect the brand image of the name Merpati Training Center, evidenced by the value of t arithmetic and t table equal to or greater than 1.96. Mar- keting strategy to increase the number of learners in Pigeons training Center is the price offered by Merpati TarininTraining should be able to compete as a certified institution in the field of aviation, and promot- ing more intensive in order to increase the number of learners and not just promoting the environment of the airline industry, but also to the general public.